The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1158/1940-6207.capr-15-0213
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Fiber-optic Raman Spectroscopy for Real-Time In Vivo Detection of Gastric Intestinal Metaplasia during Clinical Gastroscopy

Abstract: We report a unique simultaneous fingerprint (FP) and highwavenumber (HW) Raman spectroscopy technique coupled with a beveled fiber-optic Raman probe for improving in vivo detection of gastric intestinal metaplasia (IM)-precancerous lesions in realtime during clinical gastroscopy. A total of 4,520 high-quality in vivo FP/HW gastric Raman spectra (normal ¼ 4,178; IM ¼ 342) were acquired from 157 gastric patients undergoing endoscopic examination. Multivariate diagnostic algorithms based on principal components a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…The receiver operating characteristic (ROC) curve analysis showed that FP/ HW Raman technology gave an area under the ROC curve (AUROC) of 0.92 (FP: 0.89, HW: 0.86) for gastric intestinal metaplasia classification. 57 …”
Section: Raman Spectroscopymentioning
confidence: 99%
“…The receiver operating characteristic (ROC) curve analysis showed that FP/ HW Raman technology gave an area under the ROC curve (AUROC) of 0.92 (FP: 0.89, HW: 0.86) for gastric intestinal metaplasia classification. 57 …”
Section: Raman Spectroscopymentioning
confidence: 99%
“…The enhanced clustering accuracy using hybrid RS‐OCT technique can be explained by its capability to simultaneously uncover both the rich biochemical and biomolecular information (ie, proteins, lipids, DNA and water content, etc.) with FP/HW RS and complementary tissue morphology information (eg, attenuation coefficients) represented by the OCT imaging . Most noticeably from the above analysis (Tables ), the alveolar process is classified with a significant higher sensitivity than other anatomical locations, signifying that the alveolar process has a unique morphology (Figures and ) and molecular profile (Figures and ) compared to the lateral tongue and floor of the mouth.…”
Section: Discussionmentioning
confidence: 91%
“…Prominent FP Raman peaks were identified in the oral cavity as follows: 853 cm −1 ( v (C─C) proteins), 1004 cm −1 ( ν s (C─C) ring breathing of phenylalanine), 960 cm −1 ( ν s (P─O) of hydroxyapatite), 1078 cm −1 ( ν (C─C) of lipids), 1265 cm −1 (amide III v (C─N) and δ(N─H) of proteins), 1302 cm −1 (CH 2 twisting and wagging of lipids), 1445 cm −1 ( δ (CH 2 ) deformation of proteins and lipids) and 1655 cm −1 (amide I v (C═O) of proteins) in the FP range . In the HW range, intense Raman peaks are also observed: that is, 2850 and 2885 cm −1 (symmetric and asymmetric CH 2 stretching of lipids), 2940 cm −1 (CH 3 stretching of proteins) and the broad Raman band of water (OH stretching vibrations peaking at ~3250 and ~3400 cm −1 ) that are related to the local conformation and interactions of OH‐bonds in the intracellular and extracellular space of oral tissue . The difference Raman spectra (ie, lateral tongue − floor of mouth, alveolar process − floor of mouth, and alveolar process − lateral tongue) ± 1SD (shaded area) are shown in Figure B.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations